Analisis Pendapatan dan Kelayakan Usahatani Jagung Hibrida - Fadil, Muhammad; Fitriana, Widya; Khairati, Rusda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Hybrid corn has high productivity and contributes to the growth of the animal feed industry. However, farmers' use of hybrid corn varieties still needs improvement. Farmers have complained about the relatively high price of hybrid corn seeds. Pesisir Selatan Regency is one of the leading corn producers in West Sumatra. In 2022, the corn production reached 203,028.00, the second highest after West Pasaman. However, the productivity is only 6 tons/ha, which is still low compared to the potential productivity of hybrid corn, which is 10-12 tons/ha. The productivity achievements are related to the technical culture farmers apply and their income and feasibility. This study aims to (1) describe the technical culture of hybrid corn and (2) analyze the income and feasibility of hybrid corn farming. The research was carried out in the "Pesisir Selatan" Regency, which is one of the leading producers of hybrid corn in West Sumatra. Data was collected by observation and interviews with 50 farmers, PPL, collector traders, and production input suppliers. The variables observed were related to technical culture, land area, amount of production, selling price, costs paid, and farming costs. Data collection was carried out in the last planting season. The data were analyzed by comparing the suitability of technical culture with Good Agricultural Practices (GAP), income analysis, and income and profit analysis. The study shows that farmers' technical culture is partially influenced by GAP, especially in embroidery, seeding, and fertilization activities. The income received by farmers reached Rp. 17,737,815.71/Ha/MT, and profits amounted to Rp. 8,022,822.02/Ha/MT. Hybrid corn farming has an R/C value of 1.34, making it feasible and profitable for farmers.